"Ancient Volscian Border Dispute Flares": REPRESENTATIONS OF MILITARISM, MASCULINITY AND THE BALKANS IN RALPH FIENNES' CORIOLANUS. Issue 3 (2nd July 2016) - Baker, Catherine
Abstract: Reception of the 2012 film adaptation of Shakespeare's Coriolanus, directed by and starring Ralph Fiennes, dealt with two particular themes: the homoerotic relationship between Fiennes' Coriolanus and the rebel leader Aufidius whose forces he eventually joins, and the choice to shoot the film in Serbia and Montenegro. While south-east Europe has become an increasingly popular location for Anglophone filmmaking, the promotion and reception of Coriolanus foregrounded the significance of Belgrade and the Balkans as a site of recent conflict. Moreover, the film constructs the world of Coriolanus and Aufidius through simulating or even re-using images of "Balkan" space with which viewers have already become familiar through news media, and it therefore draws on and contributes to representative practices that constitute the Balkans as a violent and warlike zone. Yet Aufidius' rebel force resembling militias from the Yugoslav wars is opposed to a highly disciplined "Roman" military equipped for urban warfare in 2000s Iraq. This article contends that the film achieves this contrast primarily through evoking different military masculinities associated with each force, which have been widely disseminated through still and filmed war photography, and secondarily through its use of specific ex-Yugoslav landscapes and cityscapes. The complex relationship between images of the Balkans, masculinity and military discipline in Coriolanus shows that images of military masculinities juxtaposed with a post-Yugoslav material environment continue to operate as symbolic resources in a contemporary western imaginary of war.